Everyday stories : the literary agenda - Bowlby, Rachel, 1957- (Literary agenda., 2016)
Ordinary life is full of words, images, and stories: we spend our days talking and writing about what's going on, and what has happened. Rachel Bowlby makes us think again about this life: always the same, always slightly changing. Drawing out the stories that surround us, she explores everyday stories, old and new-in literature and in real life.